Organising the unthinkable in times of crises: Will climate engineering become the weapon of last resort in the Anthropocene?. (July 2018) - Lederer, Markus; Kreuter, Judith
In this article, we ask how the approaches of climate engineering – mostly highly technological approaches to address the challenge of global climate change – might be organised in the age of the Anthropocene. We understand the term 'Anthropocene' to be characterised by crisis, on one hand, and by promise, on the other. In particular, we aim to raise doubts on the dominant perspective on the organisation of climate engineering, which assumes these approaches to be regulated through legalistic means. Drawing an analogy to the early development stages of nuclear weapons, we point out that, instead of following a legalistic rationale, climate engineering organisation might pursue a logic of technical feasibility, political acceptance and bureaucratic momentum.